Bilateral pulmonary emboli in an amateur kick boxer: A case report and literature review. Issue 9 (30th August 2021) - Abdelmahmuod, Elabbass A.; Alzibdeh, Aseel; Rahil, Ali
Abstract: Increased knowledge of unusual pulmonary embolism presentations in athletes will prevent delays in the diagnosis and management. Abstract : Increased knowledge of unusual pulmonary embolism presentations in athletes will prevent delays in the diagnosis and management.